Comparison of full sib, half sib and S,progenies in fennel (Foeniculum vulgare Mill.) - Singhania, V V Singh, E V Divakara Sastry, D L (Journal of Spices and Aromatic Crops, 2004)
A field experiment was conducted at Jobner (Rajasthan), to compare different population improvement methods in a fennel (Foeniculum vulgare) population namely, UF-143. Estimates of genotypic coefficient of variation and phenotypic coefficient of variation were higher in full sib than S1 and half sib progenies for most of the traits. Heritability estimate was higher in full sib progenies for days to 50% flowering, seeds umbel-1 and test weight, while half sib showed maximum heritability for branches plan-1, umbels plan-1 and umbelletes umbel-1. S1 progenies recorded maximum heritability and genetic gain for seed yield plant-1. For most of the traits, full sib progenies recorded maximum genetic gain except plant height, umbellets umbel-1 and seed yield plant-1.